Garbage Island - Koehler, Fred (Koehler, Fred. Nearly always perilous adventures of Archibald Shrew., 2018)
"In the midst of the Great Pacific Garbage Patch, Archibald Shrew and Garbage Island's mouse mayor, Mr. Popli, constantly clash over Archibald's bungled inventions. In fact, Archie and Mayor Popli are so busy arguing that they don't realize their island is falling apart until it's too late. Caught in a current, these unlikely companions are swept far from home on a rip-roaring adventure neither could have imagined. As they try to fight their way back, they'll face many perils--a massive storm, deadly predators, a formidable enemy army--and discover new strengths in themselves and each other. But they'll need every ounce of bravery, creativity, and cooperation they can muster--if they're going to survive."--Dust jacket front flap.